S4.5b A randomized, double blind phase II proof-of-concept superiority trial of fosravuconazole 200 mg or 300 mg weekly dose versus itraconazole 400 mg daily, all three arms in combination with surgery, in patients with eumycetoma in Sudan—pharmacokinetic results. (20th September 2022) - Brüggemann, Roger; Nyaoke, Borna; Ahmed, Eiman Siddig; Siddig, Emanwell Edwar; Egondi, Thaddaeus; Oyieko, Peelen; Bakhiet, Sahar Mubarak; Zijlstra, Eduard E; Fahal, Ahmed H
Abstract: S4.5 Mycetoma Clinical Trial on fosravuconazole treatment in eumycetoma– Top Line Results, September 22, 2022, 10:30 AM - 12:00 PM: Objective: To evaluate the pharmacokinetics (PK) of fosravuconazole (measured as ravuconazole) and itraconazole in patients with mild to moderate eumycetoma caused by Madurella mycetomatis using a non-compartmental PK analysis. Methods: Participants received either 200 mg or 300 mg ravuconazole once weekly or 400 mg itraconazole daily for a total duration of 12 months. Plasma concentrations of ravuconazole and itraconazole were measured on day 1 of week 1, and on weeks 2, 3, 4, and months 2, 3, 6, and 12 (at end of treatment) for analysis of population PK. The exact time of dosing on the days of sample collection, and the exact time of sample collection within the collection time window, were recorded. Plasma concentrations were quantified using Ultraperformance Liquid Chromatography with fluorescence detection (UPLC-UV). Ravuconazole and itraconazole plasma concentration-time data was performed using a standard two stage approach with non-compartmental analysis. Derived exposure parameters of ravuconazole and itraconazole, including, but not limited to, Cmax and AUC at steady state (AUCs), were calculated. The effect of covariates, such as baseline characteristics/demographics, on PK were explored. AUCs were determined when at least three subsequent samples within one dosing interval were available. Results: A total of 766 samples of ravuconazole in 68 participants and 226 samples of itraconazole in 36 participants were analyzed. The average concentration of ravuconazole (range) was 3.1 mg/l (0.01-12.33 mg/l), and for itraconazole was 1.59 mg/l (0.01-5.53 mg/l). Detailed Pharmacokinetic results will be communicated and discussed in the oral presentation.